Professional Development Needs of Private and Public High Schools EFL Teachers in Erbil-Kurdistan - Professional Development Needs of Private and Public High Schools EFL Teachers in Erbil-Kurdistan Mawdud Ibrahim; Kavlu, Aziza (International journal of social sciences & educational studies, 2020)
Due to the importance of professional development in the improvement of teaching and education, and the importance of English as a language and subject of study in Erbil, this study focused on the needs for professional development of English teachers. The present study also investigated teachers’ opinions about their needs for professional development. The study also attempted to explore other issues related to the professional development of teachers of English in Erbil such as benefits of professional development programs, state of professional development programs, stages of applying for professional development programs and problems in professional development programs. 36 English language teachers participated in a survey. The survey results demonstrated that a great number EFL teachers are aware of the importance of professional development. However, lack of resources and opportunities are some of the major reasons which prevent them to participate in professional development activities. The present study attempts to reveal what EFL teachers think about their professional development and what kind of difficulties they face in pursuing their goals.